Kapasitas Organisasi Pemerintahan Desa - Oktavia, Try Amara; Nurasa, Heru (JOPPAS: Journal of Public Policy and Administration Silampari, 2024)
This research aims to determine the organizational capacity of the Mekarsari Village Government in Cikajang District, Garut Regency. The research method used is qualitative. The results of this research indicate that organizational capacity has not been fulfilled. This is due to the lack of existing facilities and infrastructure so that the public services provided are still not effective and efficient, human resources still do not understand their main duties and tasks and have not been able to complete their tasks in a timely manner, lack of transparency and weak communication with citizens regarding development programs in Mekarsari Village so that there are misconceptions in the development plans carried out in the Village. The suggestion in this research is to look for other ways to increase the human resource capacity of staff, implement development programs optimally and involve community participation regarding development programs. Keywords: Organizational Capacity, Public Organizations, Village Government